Representasi Anarkisme Dalam Film Serial Money Heist Season 1 & 2 - Marbun, Angelina Sellyn Manora; Nugroho, Wahyu Budi; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This research aims to analyze the representation of anarchism presented in seasons 1 and 2 of the series Money Heist. The primary focus of this series is on acts of robbery with an anarchist twist. The approach used in this analysis refers to the framing analysis developed by Zhongdan Pan and Gerald M. Kosicki. The findings of this analysis indicate that Money Heist portrays various tenets of anarchism, particularly the postmodern perspective. Data extracted from various scenes in the Money Heist series reveal two central concepts in postmodern anarchism: the moral legitimacy challenged by the state and the role of media as a tool of control wielded by the state. From this research, it can be concluded that Money Heist conveys the message that anarchism is not solely about destructive actions but also serves as a form of resistance against injustice and the abuse of power perpetrated by the state and excessive authorities.